A time-dependent quantum study of $Li+ HF(\\nu=1) \ ightarrow LiF(\\nu^{'}) +H $ - Göğtaş, Fahrettin; Balınt-kurtı, Gabriel G. (My University, 1998)
Time-dependent quantum wave packet calculations are performed for a model based (two-dimensional) $Li+ HF(\\nu=1) \\rightarrow LiF(\\nu^{'}) +H $ action. The reaction probabilities for a broad range of collison energies are calculated by a single solution of the time-dependent Schrödinger equation. The calculated reaction probabilities show many sharp features as a function of energy which are ascribed to scattering resonances.
Keywords: Fizik; Uygulamalı; Fizik; Atomik ve Moleküler Kimya